Analysis of the Effect of Unemployment Rate, Economic Growth, and Human Development Index on Poverty in Districts/Cities of North Sumatra Province - Titi Resnawati Nazara; Ni Putu Martini Dewi (International Forum of Researchers and Lecturers, 2025)
Poverty is a complex and multidimensional problem. It can be characterized as a condition in which there is a lack of aspects related to the quality of life. North Sumatra Province is known as one of the richest provinces in Indonesia with abundant natural resources and agricultural products such as petroleum, natural gas, palm oil, rubber, and forest products used as industrial materials. However, it still ranks among the provinces with the highest poverty rates in Indonesia. This study aims to analyze the effect of unemployment rate, economic growth, and Human Development Index (HDI) on poverty in 14 districts/cities of North Sumatra Province during the 2016–2023 period. The analytical method used is panel data regression with the Fixed Effect Model (FEM) approach. The results of this study indicate that simultaneously, the three independent variables have a significant effect on poverty. Partially, unemployment has a positive and significant effect, while economic growth and HDI have no significant effect on poverty.